Using a patient prompt list to raise concerns in oncology clinics does not necessarily lead to longer consultations. Issue 9 (November 2020) - Rogers, S.N.; Semple, C.; Humphris, G.M.; Lowe, D.; Kanatas, A.
Abstract: Head and neck oncology post-treatment consultations form a critical component of care in terms of support and surveillance. They occur frequently in the first few years and can place substantial demands on healthcare resources. However, they provide useful opportunities for patients to raise issues and receive tailored information and support. The aim of this paper was to assess whether completion of a 56-item patient prompt list (PCI - the Patient Concerns Inventory) immediately prior to the consultation significantly increased its duration. This was a pragmatic cluster preference randomised controlled trial of 288 patients with 15 consultant clusters from two sites "using" (n = 8) or "not using" (n = 7) the PCI. Consultation times were known for 283 patients (136 PCI, 147 non-PCI) who attended their first post-treatment trial consultation a median (IQR) of 103 (70-160) days after the end of treatment. Consultations lasted a median (IQR) of 10 (7-13) minutes (mean 11) in non-PCI patients and a median (IQR) of 11 (8-15) minutes (mean 12) in PCI patients (p = 0.07). After adjustment for patient clustering and significant case mix, the 95% confidence interval for the mean difference was between 1.45 minutes shorter with the PCI and 2.98 minutes longer (p = 0.50). There was significant variation in duration by consultant, tumour stage, treatment mode, overall quality of life (QoL), and distress (all p < 0.001). In those who completed the PCI, duration increased with the total number of items selected (p < 0.001). In conclusion, the inclusion of a prompt list to help facilitate conversation with patients did not make a substantial difference to consultation times.